INDICATIONS AND DIRECTIONS OF DEVELOPMENT OF DNA EXAMINATION - Kamoliddinova , Feruza Kamoliddin qizi; Akbarov , Navro‘z Jahongir o‘g‘li (Educational Research in Universal Sciences, 2023)
The article discusses the indications and directions of development of DNA examination, focusing on its importance in forensic investigations. The authors provide an overview of the history and development of DNA examination techniques, including polymerase chain reaction (PCR), short tandem repeat (STR) analysis, and single nucleotide polymorphism (SNP) analysis. They also discuss the advantages and limitations of these techniques, as well as their application in forensic casework.The article emphasizes the importance of proper interpretation of DNA examination results and the need for standardization of procedures and protocols to ensure accuracy and reliability of the results. The authors also highlight the potential future directions of DNA examination, such as the use of advanced technologies like next-generation sequencing (NGS) and the integration of DNA examination with other types of forensic analysis.